A Look at the Approaches to Multicultural and Anti-Racist Education Through the Lenses of Critical Race Theory: The Reported Benefits and Failures - Rawia Azzahrawi (Journal of Advanced Research in Education, 2022)
Multicultural and anti-racist education are pedagogies developed to include all students, despite their cultural and lingual backgrounds. As educative pedagogies, they recognize the importance of ethnic and cultural diversity in affecting people’s existence, social involvements, identities, and educational opportunities (Gay, 2004). This paper presents various approaches that encourage curriculum reform through the lens of Critical Race Theory (CRT). The paper highlights the efficacy of the different approaches in providing equal opportunities for students from diverse racial, ethnic, linguistic, and cultural backgrounds to succeed academically.